Inverse modeling of thermal boundary conditions in commercial aircrafts based on Green's function and regularization method. (1st June 2022) - Lei, Lei; Zheng, Hao; Xue, Yu; Liu, Wei
Abstract: To quantify the thermal environment in a commercial aircraft, the accurate estimation of the thermal boundary conditions is very critical. However, there is no fast and accurate method. In this study, an inverse modeling using Computational Fluid Dynamics (CFD) combined with Green's function and regularization method is proposed to identify the convective heat transfer of inner wall by using the air temperature at monitored points in the cabin. Green's transfer matrix is used to describe the causal relationship between the monitored air temperatures and the thermal boundary conditions, which greatly improves the calculation efficiency. Due to the ill-posed nature of the inverse problem, regularization methods are used to ensure the stability of the inversion solution. This investigation compares the performance of Tikhonov, truncated singular value decomposition (TSVD) and damped generalized singular value decomposition (DGSVD). To verify the feasibility of the inverse modeling, the inner wall convective heat transfer of the cabin is solved by using the measured and simulated data in a small-scale cabin testbed and a full-scale aircraft cabin, respectively. The results show that the proposed inverse modeling can accurately and effectively determine the convective heat transfer on the inner wall. Highlights: Inverse modelling of convective heat transfer on the inner wall of aircraft cabin. Consideration of the impacts by internal and external environments. Green's function to establish the heat transfer matrix for fast solution. Tikhonov, TSVD and DGSVD regularization methods are compared and optimized. Model validation by experimental data of a small-scale aircraft cabin.